Prefixed Denominal Verbs in Indonesian Children's Story - Sotyarani Padmarintan; Tri Mastoyo Jati Kesuma (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to describe the prefixes that form denominal verbs and their meanings in Indonesian children's storybooks. Previous research tends to be general and less focused on children's production. This study examines prefixes and their meanings to describe the extent to which junior high school children master denominal verbs. With a descriptive qualitative approach, the research data in the form of sentences with denominal verb predicates are taken from the anthology Jangan Pernah Menyerah Wujudkan Mimpimu by junior high school students. The listening and note-taking methods were used for data collection, while the direct element division and paraphrasing techniques were used for affix and meaning analysis. The results show that junior high school students are able to produce denominal verbs with various prefixes. The prefix "ber-" is the most productive (274 verbs), followed by "me(n)-" (192 verbs), "ter-" (77 verbs), and "di-" (12 verbs). The dominance of ber- and me(N)- shows a tendency towards active verbs, although some verbs with ter-, such as tersenyum ‘to smile,' also function actively. Students show good morphophonemic mastery of the morphemes {ber} and {me}. The meanings of the verbs vary depending on the prefix: me(N) has 13 meanings, ber has 10 meanings, ter has 2 meanings, and di has 1 meaning. These results reflect a good command of morphology as well as a tendency towards concrete meanings and physical activities, showing students' ability to form and understand various meanings from denominal affixes.